PENGUASAAN MENULIS GURU SEKOLAH DASAR DI KOTA DAN DI KABUPATEN JAYAPURA - Normawati NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This research aims to know about writing competence of elementary school’s teacher in Jayapura City and Jayapura Municipality. The researchers want to find out competences which consist of various linguistic aspects, namely, discourse content mastery, organization, vocabulary, grammar, spelling and writing technique. Method which is applied in this study is descriptive method by using content analysis. The finding shows us that writing competence of elementary school teacher in Jayapura is good. They can generally describe discourse content vast and complete; even though they lack of spelling competence and word writing technique so that it obscures the meaning of sentence. But, they have capability in arranging and organizing a writing. They writing result shows an ordered and clear one. It has many ideas, logical sequence, and good cohesion.  They also master vocabulary and are able to arrange a simple sentence though it has few grammar mistakes but it doesn’t obscure the meaning; they have vast vocabulary, using effective sentence as well as constructing and choosing correct words.